Leukol Dark Green Dye Bottle - Science History Institute (2017)
Round glass bottle with cork stopper; label attached to front identifies manufacturer and contents (label has been waxed over); bottle is half full with original dye.
Keywords: Dye industry; Textile industry; Dyes and dyeing; Farbenfabriken vorm. Friedrich Bayer & Co.